Cyclic oscillations of basal plasma glucose and insulin concentrations in human beings. - Lang, D; Matthews, DR; Peto, J; Turner, R (1979)
In a study of whether oscillations in plasma glucose and insulin occur in human beings, plasma samples were taken at one-minute intervals from 10 normal subjects for periods lasting between one and two hours. In five subjects the basal plasma insulin concentrations cycled regularly, with a mean period of 13 minutes and mean amplitude of 1.6 mU per liter (11.5 pmol per liter). A concurrent plasma glucose cycle was demonstrated, with a mean amplitude (after averaging to minimize random error) of 0.05 mmol per liter (1 mg per decliter). The average plasma glucose cycle was two minutes in advance of the plasma insulin. In the subjects with less regular plasma insulin cycles, a similar plasma glucose rise was demonstrated two minutes before the insulin rise. These phase relations are compatible with the presence of a negative-feedback loop between the liver and pancreatic beta cells that regulates both basal plasma insulin and glucose concentrations, although the cyclic beta-cell secretion could be independent of plasma glucose.